Prenatal anxiety and obstetric decisions among pregnant women in Wuhan and Chongqing during the COVID‐19 outbreak: a cross‐sectional study. (2nd August 2020) - Liu, X; Chen, M; Wang, Y; Sun, L; Zhang, J; Shi, Y; Wang, J; Zhang, H; Sun, G; Baker, PN; Luo, X; Qi, H
Abstract : Objectives: To investigate the mental status of pregnant women and to determine their obstetric decisions during the COVID‐19 outbreak. Design: Cross‐sectional study. Setting: Two cities in China––Wuhan (epicentre) and Chongqing (a less affected city). Population: A total of 1947 pregnant women. Methods: We collected demographic, pregnancy and epidemic information from our pregnant subjects, along with their attitudes towards COVID‐19 (using a self‐constructed five‐point scale). The Self‐Rating Anxiety Scale (SAS) was used to assess anxiety status. Obstetric decision‐making was also evaluated. The differences between cities in all of the above factors were compared and the factors that influenced anxiety levels were identified by multivariable analysis. Main outcome measures: Anxiety status and its influencing factors. Obstetric decision‐making. Results: Differences were observed between cities in some background characteristics and women's attitudes towards COVID‐19 in Wuhan were more extreme. More women in Wuhan felt anxious (24.5 versus 10.4%). Factors that influenced anxiety also included household income, subjective symptom and attitudes. Overall, obstetric decisions also revealed city‐based differences; these decisions mainly concerned hospital preference, time of prenatal care or delivery, mode of delivery and infant feeding. Conclusions: The outbreak aggravated prenatal anxiety and the associated factors could be targets for psychological care. In parallel, key obstetric decision‐making changed, emphasising the need for pertinent professional advice. Special support is essential for pregnant mothers during epidemics. Tweetable abstract: The COVID‐19 outbreak increased pregnant women's anxiety and affected their decision‐making. Tweetable abstract: The COVID‐19 outbreak increased pregnant women's anxiety and affected their decision‐making. This article includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights16381